Controlling the Surface Chemistry of Multiwalled Carbon Nanotubes for the Production of Highly Efficient and Stable Laccase-Based Biocatalysts - Cláudia G. Silva (2014)
Laccase was immobilized over multiwalled carbon nanotubes (MWCNTs) with diameters ranging from 10 to 100 nm and different surface chemical groups. Oxygen-containing groups were introduced selectively or removed by liquid-phase oxidation and thermal treatments. The effect of pH on the immobilization efficiency and catalytic activity of laccase has been evaluated. Pristine MWCNTs show excellent immobilization capacity (100%) and high enzyme activity, but low thermal stability (at 50 degrees C) owing to weak interaction (mostly hydrophobic) be-tween laccase and the support. Immobilization capacity and catalytic activity of laccase on the modified MWCNTs were related to the surface electric charge of both the support and the enzyme. MWCNTs oxidized with HNO3 and posteriorly heated at 400 degrees C, mostly presenting hydroxyl surface groups, provided the best compromise between laccase activity and thermal stability, which has been attributed to the formation of hydrogen bonds between the support and the enzyme.